Resource Elements In The Construct Of Special Education Teacher Workload In Malaysia - et. al., Farah Adibah binti Ibrahim, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Among the most important elements present in the construct of teacher workload that provide a significant relationship to teacher job satisfaction is the resource element. This note illustrates that the resources available in coping with the workload, are positively correlated with teacher job satisfaction. These findings are in line with several previous studies stating that the resources supplied can alleviate stress on teachers. This situation can make them more prepared in carrying out tasks and enjoy satisfaction in performing assigned tasks. This qualitative study was conducted to detail teachers' perceptions of the resource elements that burden their assignments. A total of 11 respondents were involved in the interview session. Based on these findings, it is hoped that the headmasters who manage the school can provide sufficient resources for the purpose of teaching teachers, and at the same time teachers also need to prepare themselves by being ready to carry out assignments.